Mendekatkan Yang Jauh, Menjauhkan Yang Dekat Dalam Kesadaran Berkomunikasi - Suryani, Cahya (Universitas Darussalam Gontor Bekerjasama Dengan ASPIKOM, 2017)
The development of technology give a big change to the interpersonal communty as face to face. Long time ago, people who are in crouded places will communicate with each other around them, but now in the crouded places we can see many people with their gadget and seems to ignore each other with the people around them. The use of gadget when people meet each other give a big influence and a different feel of comunity. The phenomena of communication awareness will be analyzes using the descriptive qualitative method and using the interpersonal comunication theory and awareness. The result of this research which was conducted that the interpersonal comunication face to face which was done simultaneously and using gadget do not have an effectiveness in communication, the main idea of the communication will not be able to reach. The communication which was made simultaneously is one of the low awareness because of the automatical processes in human body.